2011
DOI: 10.3892/ijo.2011.1075
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation hybridization profiling identifies involvement of STAT1-mediated pathways in breast cancer

Abstract: Abstract. Many cancer-related genes are regulated by an epigenetic mechanism through modification of the methylation status of CpG sites at the promoter. This study was carried out at a genome-wide scale to mine genes in which the methylation of CpG sites is altered in breast cancer tissues. Differential methylation hybridization analysis was conducted using a chromosomal DNA mixture of ten normal and cancer tissue sets. A CpG microarray harboring 237,220 CpG sites of the whole genome was interrogated and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…siRNA-mediated knockdown of RPIA resulted in reduced cell growth in Hep3B and PLC5 liver cancer cell lines. However, RPIA may play an inhibitory role in the progression of some tumors, as increased hyper methylation of the RPIA locus has been observed in breast cancer [23] . Furthermore, it has been shown that microRNAs can target the RPIA gene and the downstream PRPS1 gene that drives nucleoside formation from ribose-5-phosphate, leading to reduced PPP flux and proliferation in human colorectal cancer cells [37] .…”
Section: Discussionmentioning
confidence: 99%
“…siRNA-mediated knockdown of RPIA resulted in reduced cell growth in Hep3B and PLC5 liver cancer cell lines. However, RPIA may play an inhibitory role in the progression of some tumors, as increased hyper methylation of the RPIA locus has been observed in breast cancer [23] . Furthermore, it has been shown that microRNAs can target the RPIA gene and the downstream PRPS1 gene that drives nucleoside formation from ribose-5-phosphate, leading to reduced PPP flux and proliferation in human colorectal cancer cells [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Van der Auwera et al (2010) Kamalakaran et al (2011) identified several hundred differentially methylated loci between 11 adjacent nonmalignant breast tissues and 108 tumors (Table 1). Kim et al (2011b) pooled DNA from ten cancers and ten nonmalignant matched adjacent tissues and identified 1181 differentially methylated CpGs (corresponding to 1043 genes) with the vast majority (972) hypermethylated (Table 1). Hill et al (2011) found 291 probes (264 genes) hypermethylated in breast cancer (nZ39) compared with non-malignant breast tissue (nZ4) after removal of imprinted genes and X chromosome genes (Table 1).…”
Section: Limitations and Biases Of Genome Wide Dna Methylation Technimentioning
confidence: 99%
“…HIST1H4L was also found to be hypermethylated in hepatocellular carcinoma tissues and triple negative breast cancer cells ( 50–52 ). Hypermethylation of specific histone isoforms genes have also been discussed in multiple other reports including Hist1H2BK in breast cancer and constitutive methylation of HIST1H2AA in a Phase I trial of azacytidine treatment for resectable gastric and esophageal adenocarcinoma patients ( 53 , 54 ). Therefore, these results suggest that histone isoforms are subject to individualized regulation at transcriptional and posttranscriptional levels and may have distinct cellular functions.…”
Section: Discussionmentioning
confidence: 94%